Production of Uniform Cloth and Military Uniforms in Russia (1698–1762). (3rd July 2021) - Ivleva, Victoria
Abstract : This article studies a corpus of state decrees aimed at regulating production of uniform cloth and military uniforms in Russia in the period between the reign of Peter I (1682–1725) and Peter III (1762). It discusses developments and challenges faced by this nascent textile industry and their wider social and cultural implications.